2020
DOI: 10.1021/acs.inorgchem.9b03335
|View full text |Cite
|
Sign up to set email alerts
|

Solvent-Induced Encapsulation of Cobalt(II) Ion by a Boron-Capped tris-Pyrazoloximate

Abstract: Boron-cross-linked cobalt(II) pseudoclathrochelate was obtained by the template reaction of 2-acetylpyrazoloxime, phenylboronic acid, and a new DMF cobalt(II) solvato complex with a decachloro-closo-decaborate dianion. As confirmed by singlecrystal X-ray diffraction, this complex crystallizes with two symmetry-independent cobalt(II) pseudoclathrochelate cations, one decachloro-closo-decaborate dianion, one benzene, one dichloromethane solvent molecule, and two molecules of DMF. The latter act as pseudocapping … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 45 publications
0
16
0
Order By: Relevance
“…An attempted crystallization of the complex 2 with an H‐bonded DMF molecule (Scheme ) from its solution in a chloroform‐heptane mixture, which was left for some time on a sunlight in air, unexpectedly produced yellow crystals of a chloroform solvate of the complex 1 earlier synthesized by our group.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…An attempted crystallization of the complex 2 with an H‐bonded DMF molecule (Scheme ) from its solution in a chloroform‐heptane mixture, which was left for some time on a sunlight in air, unexpectedly produced yellow crystals of a chloroform solvate of the complex 1 earlier synthesized by our group.…”
Section: Resultsmentioning
confidence: 99%
“…Although it is generally accepted that (pseudo)clathrochelates of transition metals can be easily obtained by a simple template condensation of appropriate oximes, boronic acids and metal salts, our study clearly shows that other compounds can be sometimes identified among the products of their synthesis or chemical transformations occurring in different media. Therefore, a further insight (such as from powder X‐ray diffraction or in situ paramagnetic NMR spectroscopy) is needed for optimizing of synthetic pathways towards this unique class of transition metal complexes for their future SMM and MRI applications.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations